The impact of INGOs and governmental assistance on women entrepreneurs’ financial performance - Rahmatullah Pashtoon; Noorihsan Bin Mohamad; Zarinah Hamid (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to explore and analyze the effects of International Non-Governmental Organizations (INGOs) and governmental assistance programs on the financial performance of women entrepreneurs. It assesses how different forms of support contribute to the economic empowerment and success of women-led businesses.Method — The study utilized an exploratory and descriptive research methodology, incorporating primary data. It surveyed 308 autonomous female entrepreneurs in Kandahar, Afghanistan using a cross-sectional questionnaire. The study employs purposive sampling and an OLS statistical model using IBM SPSS V.27.Result — The findings indicate that support programs from INGOs and government assistance positively and significantly influence the financial performance of women-run businesses in terms of profitability volume, average annual sales, return on investment, and inventory turnover.Practical implications — The research emphasizes the crucial role of International Non-Governmental Organizations (INGOs) and government aid programs in enhancing the economic success of female entrepreneurs. Policymakers, INGOs, and local government organizations should concentrate on creating specialized support programs that provide financial assistance, training, and resources customized for women-led companies in socio-economically disadvantaged regions. These findings promote extending support programs to additional areas, highlighting the importance of ongoing and customized help to ensure the endurance and development of women's entrepreneurship. This approach aids in economic empowerment and promotes broader socio-economic progress by assisting women entrepreneurs in overcoming specific obstacles and benefiting their communities.